Is intuitive eating the same as flexible dietary control? Their links to each other and well-being could provide an answer. (1st December 2015) - Tylka, Tracy L.; Calogero, Rachel M.; Daníelsdóttir, Sigrún
Abstract: Researchers have found that rigid dietary control is connected to higher psychological distress, including disordered and disinhibited eating. Two approaches have been touted by certain scholars and/or health organizations as healthier alternatives: intuitive eating and flexible control—yet these approaches have not been compared in terms of their shared variance with one another and psychological well-being (adjustment and distress). The present study explored these connections among 382 community women and men. Findings revealed that intuitive eating and flexible control are inversely related constructs. Intuitive eating was related to lower rigid control, lower psychological distress, higher psychological adjustment, and lower BMI. In contrast, flexible control was strongly related in a positive direction to rigid control, and was unrelated to distress, adjustment, and BMI. Further, intuitive eating incrementally contributed unique variance to the well-being measures after controlling for both flexible and rigid control. Flexible control was positively associated with psychological adjustment and inversely associated with distress and BMI only when its shared variance with rigid control was extracted. Collectively, these results suggest that intuitive eating is not the same phenomenon as flexible control, and that flexible control demonstrated substantial overlap and entanglement with rigid control, precluding the clarity, validity, and utility of flexible control as a construct. Discussion addresses the implications of this distinction between intuitive eating and flexible control for the promotion of healthy eating attitudes and behaviors. Highlights: We explored links between intuitive eating and flexible control with community adults. Intuitive eating and flexible control are qualitatively distinct constructs. Flexible and rigid control were strongly and positively related and not distinct. Intuitive eating accounted for unique variance in psychological well-being and BMI. Flexible control accounted for unique variance only when rigid control was extracted.